Phase‐Separated Polyzwitterionic Hydrogels with Tunable Sponge‐Like Structures for Stable Solar Steam Generation. (1st February 2023) - Peng, Bolun; Lyu, Quanqian; Li, Miaomiao; Du, Shuo; Zhu, Jintao; Zhang, Lianbin
Abstract: Solar steam generation (SSG) through hydrogel‐based evaporators has shown great promise for freshwater production. However, developing hydrogel‐based evaporators with stable SSG performance in high‐salinity brines remains challenging. Herein, phase‐separated polyzwitterionic hydrogel‐based evaporators are presented with sponge‐like structures comprising interconnected pores for stable SSG performance, which are fabricated by photopolymerization of sulfobetaine methacrylate (SBMA) in water‐dimethyl sulfoxide (DMSO) mixed solvents. It is shown that driven by competitive adsorption, the structures of the resulting poly(sulfobetaine methacrylate) (PSBMA) hydrogels can be readily tuned by the volume ratio of DMSO to achieve phase separation. The optimized phase‐separated PSBMA hydrogels, combining the unique anti‐polyelectrolyte effects of polyzwitterionic hydrogels, demonstrate a rapid water transport capability in brines. After introducing photothermal polypyrrole particles on the surface of the phase‐separated PSBMA hydrogel evaporators, a stable water evaporation rate of ≈2.024 kg m −2  h −1 and high solar‐to‐vapor efficiency of ≈97.5% in a 3.5 wt.% brine are obtained under simulated solar light irradiation (1.0 kW m −2 ). Surprisingly, the evaporation rates remain stable even under high‐intensity solar irradiation (2.0 kW m −2 ). It is anticipated that the polyzwitterionic hydrogel evaporators with sponge‐like porous structures will contribute to developing SSG technology for high‐salinity seawater applications. Abstract : A phase‐separated polyzwitterionic hydrogel with tunable sponge‐like structures is developed as an evaporator for stable solar steam generation. A stable water evaporation rate of ≈2.024 kg m −2  h −1 and ≈97.5% solar‐to‐vapor efficiency in a 3.5 wt.% brine can be achieved with the evaporator. These artfully designed phase‐separated polyzwitterionic hydrogels may assist in constructing evaporators for high‐salinity brines.